Pulmonary Tuberculosis in Immunocompromised Patients: A Review - Bittugondanahalli Prakash, Lohith Kumar; Mane, Manisha; Sahu, Shalini; Vimala, Leena Robinson; Jha, Pallavi; Rebecca, Grace; Manoharan, Aishwarya; Irodi, Aparna (Indographics, 2024)
Tuberculosis (TB) remains a leading cause of morbidity and mortality worldwide and in India. Immunocompromised individuals, including those with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS), cancer, diabetes, or those undergoing immunosuppressive therapy, are at a heightened risk of developing TB, often presenting with atypical symptoms, imaging features, and more severe disease outcomes. This review highlights the atypical radiological pattern of TB in these states. It is well recognized that there is considerable overlap of imaging findings across a variety of pulmonary infections and noninfectious processes. The presence or absence of specific indicators and consideration of clinical factors can help narrow the differential diagnoses. Thereby, it is crucial for radiologists to identify the imaging features that not only are characteristic of pulmonary TB but also interpret the atypical findings and corroborate with appropriate clinical history, especially concerning the immune status of the patient, to provide crucial information while minimizing radiation exposure and patient expenditures for the best possible care.
Keywords: immunocompromised; tuberculosis; pulmonary infections